(untitled) (Research, Society and Development, 2022)
The growing concern about climate change as well as increasingly stringent environmental legislation and the environmental degradation drive the consumption of biofuels in order to reduce polluting emissions. Ethanol obtained from from sugar cane has been widely used as it is a renewable energy source and produces low pollutant emissions. In Brazil, the Proálcool encourages the expansion of sugarcane flavors throughout the state of São Paulo and the region of Pontal do Paranapanema is showing a growing replacement of pasture areas by this crop. In this context, the present work aims to estimate the production of ethanol for a small region of Pontal do Paranapanema from the replacement of pasture areas by sugarcane crops. For this, a land use and land cover map of the region was generated through the supervised classification of an image from the Sentinel 2A satellite in Google Earth Engine using the Random Forest algorithm and the NDVI, NDBI, MNDWI and RS indices. The classification had excellent accuracy, with Kappa Index values ​​of 99.7% and overall accuracy of 99.78%. Pastures occupy 48.08% of the study area, with 196,416.71 hectares and when replacing pastures for sugar cane, the area presents a production potential between 1,079,741,938.32 and 1,214,709,680.61 liters of ethanol. Thus, the shows an enormous potential for ethanol production, being attractive for investments in the sector, favoring the economy and the population of the municipalities in the region.